The experience of constitutional mutation in Spain - Ruiz-Rico Ruiz, Gerardo (2020)
This essay examines the concept and limits of the constitutional mutation and how they affect constitutional texts. The mutation has some specials characteristics, different to the adaption. It is used to study the interpretive process of constitutional norms. It is because the mutation responds to the context. The Spanish Constitution of 1978 is a limited text, but the Court’s constitutional interpretation has recreated his significance. It happened for example in its decision on the «territorial constitution» regarding to the Spanish autonomous government. Another example, its decision on the fiscal stability: it is a new constitutional standard created through the interpretive work of the «Tribunal Constitucional». Now, fiscal stability is a new assumption of the economic crisis and it is a new constitutional component of the constitutional interpretation.